Adaptive disclosure, a combat-specific PTSD treatment, versus cognitive-processing therapy, in deployed marines and sailors: A randomized controlled non-inferiority trial. (March 2021) - Litz, Brett T.; Rusowicz-Orazem, Luke; Doros, Gheorghe; Grunthal, Breanna; Gray, Matthew; Nash, William; Lang, Ariel J.
Highlights: Adaptive Disclosure (AD) is a new combat-specific emotion-focused PTSD treatment. We conducted a randomized non-inferiority trial of AD in the military. AD was no less effective than an established first-line psychotherapy. Abstract: Adaptive Disclosure (AD) is a new emotion-focused psychotherapy for combat-related PTSD. As a second step in the evaluation process, we conducted a non-inferiority (NI) trial of AD, relative to Cognitive Processing Therapy – Cognitive Therapy version (CPT-C), an established first-line psychotherapy. Participants were 122 U.S. Marines and Sailors. The primary endpoint was PTSD symptom severity change from pre- to posttreatment, using the Clinician Administered PTSD Scale for DSM-IV. Secondary endpoints were depression (Patient Health Questionnaire-9; PHQ-9) and functioning (Veterans Rand Health Survey-12; VR-12). For cases with complete data, the mean difference in CAPS-IV change scores was 0.33 and the confidence interval (CI) did not include the predefined NI margin (95% CI =-10.10, 9.44). The mean difference in PHQ-9 change scores was -1.01 and the CI did not include the predefined margin (95% CI = -3.31, 1.28), as was the case for the VR-12 Physical Component and VR-12 Mental Component subscale scores (0.27; 95% CI = -4.50, 3.95, and -2.10; 95% CI = -7.03, 2.83, respectively). A series of intent-to-treat sensitivity analyses confirmed these results. The differential effect size for CAPS-IV was d = 0.01 (nonsignificant). As predicted, Adaptive Disclosure was found to be no less effective than a first-line psychotherapy.